List of seminars/trainings by central laboratory - Siti Nurfashiha, Mohd Yasin (Penerbit UMP, 2015)
1. Seminar on HPLC- 'Principle of HPLC, HPLC column theory and trouble shooting, sample preparation using SPE'. Date : August 21, 2015. Venue :Tun Fatimah Hall. Participant : 53 (internal and external) Project value : RM3, 180 Objective: The aim is to inform users about the HPLC (High Performance Liquid Chromatography) instruments comprising the principles, theory, column and maintenance as well as sample preparation using Solid Phase Extraction (SPE). It is carried out with the cooperation of Research Instrument (RI) Sdn. Bhd. Speaker/Trainer : Ms Chew Won Chin of RI Sdn. Bhd.